A Tentamen Suicide in Neuropsychiatric Syndrome in Severe COVID-19 Intensive Care Patient with Respiratory Failure: a Serial Cases - Suparno Adi Santika; Nancy Margaritta Rehatta; Christrijogo Sumartono (Jurnal Kesehatan Hesti Wira Sakti, 2022)
Abstract Introduction : COVID-19 is a pneumonia caused by SARS-CoV-2 infection, that can cause morbidity and mortality in the care of critical patients in the Covid-specific Intensive Care Unit (RICU). Tentamen suicide is one of severe neuro-psychiatric syndrome which can aggravate the condition of patients with acute respiratory failure. Methode : We present 3 cases of patients with suicide trial in severe COVID-19 Pneumonia accompanied by acute respiratory failure. Results : Patients with tentamen suicide experience a gradual worsening of condition. This complication especially tentamen suicide is not well recognized at the beginning of treatment. Conclusion :The conclusion of this case series is tentamen suicide is one of severe neuropsychiatric syndrome in COVID-19 patient with respiratory failure. Early recognizing and conducting clinical management of neuropsychiatric syndrome symptoms in COVID-19 Pneumonia patients with acute respiratory failure who are intensively treated at the RICU can reduce the risk of morbidity, mortality and improve patient outcomes.